Mobile Learning Applications and Their Impact on Students' Academic Performance in Rural Schools - Muhammedova, Farog‘at; Ergashev, Mirkomil; Imamova, Nilufar; Ashirova, Anorgul; Urishev, Adham; Kuvvatova, Mokhira; Sattorova, Shalola (International Journal of Engineering, Science and Information Technology, 2025)
Mobile learning is a recognised methodology due to its numerous advantages, including the ability to access educational content at any time and place, customisation of content to meet students' needs, and prompt feedback. This study aims to demonstrate that learning facilitated by a customised smartphone application can successfully improve the academic achievement of Rural School (RS) students by implementing periodic evaluations via the mobile application. This study proposed Mobile Learning Applications and their Impact on Students' Academic Performance (MLA-SAP) in RS. The study subjects were students in RS, Uzbekistan. An MLA-based approach was implemented in the test group (n?=?20), whereas the control group engaged in a lecture-based traditional classroom setting (n?=?35). An outlook scale has been employed to assess students' perceptions of mobile learning, while a test of success was utilised to evaluate the impact of MLA on student academic performance. Interviews have been conducted with RS students and teachers for a qualitative analysis. The results indicate that MLA may facilitate SAP. Both groups exhibited markedly elevated scores regarding MLA.